An elementary investigation of rolling disks - True, Otho Sprague (My University, 1899)
Introduction: The real complexity of the facts and conditions present in every consideration of rolling bodies, has generally, if not universally, been underestimated by those who have had to deal with the problem; and while practically the problem is not so serious an obstacle to mechanical progress as theoretical investigation may tend to show, yet the inappreciation of the effects of unbalanced wheels, on the mistaken idea that unbalanced wheels were balanced, has let to serious and perplexing results in some lines of engineering. I shall not attempt to solve all the combinations or problems that may arise in connection with this subject, or even to show whereby may be solved the entire question, but shall endeavor to do just two things: First, To point out the conditions that do exist in a few instances of the simplest cases of unbalanced wheels. Second, to show the effect of such conditions on the support of rail and upon the axle or shaft, if there be such effect, result on action.
Citation: True, Otho Sprague. An elementary investigation of rolling disks. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Component Velocities; Accelerations; Path Velocity; Theses; Manuscripts (documents)